Association Between Secondary Hyperparathyroidism and Body Composition in Pediatric Patients With Moderate and Advanced Chronic Kidney Disease - Karava, Vasiliki; Kondou, Antonia; Dotis, John; Christoforidis, Athanasios; Taparkou, Anna; Tsioni, Konstantina; Farmaki, Evangelia; Kollios, Konstantinos; Siomou, Ekaterini; Liakopoulos, Vassilios; Printza, Nikoleta (Frontiers in Pediatrics, 2021)
Objective: This single center cross-sectional study aims to investigate the association between secondary hyperparathyroidism and body composition in pediatric patients with moderate (stage 3) and advanced (stage 4-5) chronic kidney disease (CKD). Methods: 61 patients (median age: 13.4 years) were included. Body composition indices, including lean tissue index (LTI) and fat tissue index (FTI), were measured using multi-frequency bio-impedance spectroscopy. Muscle wasting was defined as LTI adjusted to height-age (HA) z-score <-1.65 SD and high adiposity as FTI z-score>1.65 SD. Serum mineral metabolism parameters, including serum intact parathormone (iPTH), calcium, phosphorus and 25-hydroxyvitamin D, as well as serum leptin were measured in each patient. In advanced CKD patients, the mean values of serum mineral laboratory parameters of the 6 months prior to body composition assessment were recorded, and alfacalcidol index, defined as weekly alfacalcidol dose (mcg/week) per pg/ml of iPTH x 1000, was calculated. Results: In moderate CKD (31 patients), high iPTH (>90 ng/ml) was observed in 10 (32.3%) patients and was associated with higher FTI z-score (p=0.022). Moreover, serum iPTH was negatively correlated to LTI HA z-score (rs=-0.486, p=0.006), and positively correlated to serum leptin levels (rs=0.369, p=0.041). The positive correlation between FTI z-score and iPTH (rs=0.393, p=0.039) lost significance after adjustment for serum leptin. iPTH was positively associated with high adiposity (12 patients, 38.7%) after adjustment for the other mineral metabolism parameters (OR 1.023, 95% CI 1.002-1.045, p=0.028). In advanced CKD (30 patients), no significant correlation was observed between iPTH and body composition indices and serum leptin levels. Eleven (36.7%) patients with muscle wasting presented lower alfacalcidol index (p=0.017). Alfacalcidol index ≤24 was strongly associated with muscle wasting after adjustment for CKD stage and other mineral metabolism parameters (OR 7.226, 95% CI 1.150-45.384, p=0.035). Conclusion: Secondary hyperparathyroidism is associated with high adiposity in moderate but not in advanced CKD, with leptin acting as a potential contributive factor. In advanced CKD, targeting higher alfacalcidol weekly dose per each unit of serum PTH seems beneficial for preventing muscle wasting.